The effect of modified kepok banana (Musa acuminata) starch substitution on the texture and color of steamed brownies - Prameswari, Annisa Dinda Wiedia; Sofyan, Aan Sofyan (Journal of Food and Agricultural Product, 2024)
One food component that can act as a functional food ingredient is resistant starch. Kepok bananas are a food source that has the potential to produce resistant starch and can be processed to produce food products. Method autoclaving cooling Kepok banana flour has the potential to increase the resistant starch content. This research aims to determine the effect of modified kepok banana starch substitution on texture (hardness, cohesiveness, adhesiveness and gumminess) and color (L, a and b values) of steamed brownies.The research method used was experimental research with a Completely Randomized Design (CRD) with 4 treatments varying the percentage of modified kepok banana starch substitution 0%, 25%, 50% and 75%. Data analysis using tests One Way Anova. Value research results hardness steamed brownies respectively, namely 41.28N; 49.81N; 29.01N; and 18.24N. Mark cohesiveness respectively, namely 0.19; 0.25; 0.25; and 0.34. Mark adhesiveness respectively, namely 0.22Nmm; 0.02 Nmm; 0.15nmm;and 0.61 Nmm while the value gumminess respectively, namely 16.56N; 23.73N; 10.74N; and 5.67N. The L values are 21.56; 21.71; 21.43; and 22.32. The values of a respectively are 6.31; 7; 36; 7.43; and 8.52 while the b values are respectively 8.57; 9.18; 9.53; and 10.40. The conclusion of this research is that there is an effect of modified kepok banana starch substitution on the texture profile hardness, cohesiveness and gumminess on steamed brownies. Keywords: brownies, banana kepok, resistant starch, color, texture